1999
DOI: 10.1177/101053959901100107
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and Distribution of Ocular Morbidity in Primary School Children of Rural Delhi

Abstract: A total of 679 primary school children drawn from developed southern parts and underdeveloped eastern parts of Delhi were examined for ocular morbidity. Their age range was 5-15 years and both sexes had almost equal representation. The prevalence of eye diseases was relatively high. Over 40 percent of all the children studied had one or more ocular problems. Trachoma (18%) was the most common ocular morbidity followed by vitamin A deficiency (10.6%), visual acuity < 6/9 (7.4%) and apparent/latent squint (7.4%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 1 publication
5
33
1
Order By: Relevance
“…14 In the present study, the prevalence of Vitamin A deficiency was 9.6 percent. In a study at rural North Maharashtra by Jayant D and Malathi, 25.58% Vitamin A deficiency was reported.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…14 In the present study, the prevalence of Vitamin A deficiency was 9.6 percent. In a study at rural North Maharashtra by Jayant D and Malathi, 25.58% Vitamin A deficiency was reported.…”
Section: Discussionsupporting
confidence: 44%
“…Prevalence of squint has been reported from Haryana, Rajasthan, West Bengal and Delhi. 14,26 The prevalence of ocular morbidity was more among low socio-economic group. Presence of ocular morbidity showed significant association with education, occupation and income of parent.…”
Section: Discussionmentioning
confidence: 99%
“…[17] School children 5-15 years of age, screened for eye morbidity, revealed that trachoma (18%) was the most common ocular morbidity followed by vitamin A deficiency (10.6%), refractive error (7.4%) and apparent / latent squint (7.4%). [18] In an Iranian study it was shown that the prevalence of myopia, hyperopia and astigmatism was 29. The prevalence of with-the-rule, against-the-rule, and oblique astigmatism was 14.5%, 4.8% and 1.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,10 Screening of school children is very useful because the uncorrected refractive errors influences on the academic performances of school life and also social life. The long term visual disabilities were minimized by proper eye screening programs.…”
Section: Discussionmentioning
confidence: 99%